2005
DOI: 10.1002/ptr.1597
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds fromRhodiola rosea (Crassulaceae)

Abstract: The methanol extract of the underground part of Rhodiola rosea was found to show inhibitory activity against Staphylococcus aureus. Bioactivity-guided fractionation of a 95% ethanol extract from the stems of R. rosea led to the isolation of five compounds: gossypetin-7-O-L-rhamnopyranoside (1), rhodioflavonoside (2), gallic acid (3), trans-p-hydroxycinnamic acid (4) and p-tyrosol (5). Their structures were elucidated by UV, IR, MS and NMR data, as well as by comparison with those of the literature. Compounds 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 20 publications
0
64
0
Order By: Relevance
“…Rhodiola rosea L. (Crassulaceae) (goldenroot or roseroot) grows in arctic and mountainous regions (Ming et al 2005). It has a long and global history of use (Panossian et al 2010), and is a popular natural remedy with a worldwide distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodiola rosea L. (Crassulaceae) (goldenroot or roseroot) grows in arctic and mountainous regions (Ming et al 2005). It has a long and global history of use (Panossian et al 2010), and is a popular natural remedy with a worldwide distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Some preclinical and clinical studies of R. rosea extracts have provided evidence for a number of pharmacological activities, including adaptogenic, antistress, antihypoxic, antioxidant, anticancer, learning and memory enhancing and immune and sexual stimulating effects (Petkov et al, 1986;Darbinyan et al, 2000;Ming et al, 2005;fragmentary and often not comparable due to the various extracts and different modalities of their administration (single or repeated); many are also not available in English language journals.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known to have adaptogenic properties (Brekhman & Dardymov, 1969). Recently, researchers have found that it can elevate concentrations of norepinephrine, dopamine, and serotonin in the brain, act as a nicotinic cholinergic agonist in the central nervous system, reduce the level of C-reactive protein and creatinine kinase in the blood, increase the ATP content in the muscle mitochondria, and has antiarrhythmic activity, anti-prostate cancer activity, and antibacterial activity (Maslov et al, 1998;Abidov et al, 2003Abidov et al, , 2004Ming et al, 2005).…”
Section: Introductionmentioning
confidence: 99%